Cationic disorder and Mn3þ/Mn4þ charge ordering in the B′ and B″ sites of Ca3Mn2NbO9 perovskite: a comparison with Ca3Mn2WO9 - Lopez, Carlos Alberto (2013)
We describe the preparation, crystal structure determination, magnetic and transport properties of two novel Mn-containing perovskites, with a different electronic configuration for Mn atoms located in B site. Ca3Mn3+2WO9 and Ca3Mn23+/4+2NbO9 were synthesized by standard ceramic procedures; the crystallographic structure was studied from X-ray powder diffraction (XRPD) and neutron powder diffraction (NPD). Both phases exhibit a monoclinic symmetry (S.G.: P21/n); Ca3Mn2WO9 presents a long-range ordering over the B sites, whereas Ca3Mn2NbO9 is strongly disordered. By "in-situ" NPD, the temperature evolution of the structure study presents an interesting evolution in the octahedral size (〈Mn-O〉) for Ca3Mn2NbO9, driven by a charge ordering effect between Mn3+ and Mn4+ atoms, related to the anomaly observed in the transport measurements at T≈160 K. Both materials present a magnetic order below TC=30 K and 40 K for W and Nb materials, respectively. The magneto-transport measurements display non-negligible magnetoresistance properties in the paramagnetic regime.